Lime is a new protein linking immunity and metabolism in Drosophila - Mihajlovic, Zorana; Tanasic, Dajana; Bajgar, Adam; Perez-Gomez, Raquel; Steffal, Pavel; Krejci, Alena (Developmental biology, 2019)
The proliferation, differentiation and function of immune cells in vertebrates, as well as in the invertebrates, is regulated by distinct signalling pathways and crosstalk with systemic and cellular metabolism. We have identified the Lime gene (Linking Immunity and Metabolism, CG18446) as one such connecting factor, linking hemocyte development with systemic metabolism in Drosophila. Lime is expressed in larval plasmatocytes and the fat body and regulates immune cell type and number by influencing the size of hemocyte progenitor populations in the lymph gland and in circulation. Lime mutant larvae exhibit low levels of glycogen and trehalose energy reserves and they develop low number of hemocytes. The low number of hemocytes in Lime mutants can be rescued by Lime overexpression in the fat body. It is well known that immune cell metabolism is tightly regulated with the progress of infection and it must be supported by systemic metabolic changes. Here we demonstrate that Lime mutants fails to induce such systemic metabolic changes essential for the larval immune response. Indeed, Lime mutants are not able to sustain high numbers of circulating hemocytes and are compromised in the number of lamellocytes produced during immune system challenge, using a parasitic wasp infection model. We therefore propose the Lime gene as a novel functional link between systemic metabolism and Drosophila immunity.
Keywords: buněčná diferenciace; Drosophila melanogaster; Hemocytes; larva; Immunity; Drosophila Proteins; mutace; hemocyty; Fat Body; CG18446; jaderné proteiny; tukové těleso; zvířata; lymfoidní tkáň; imunita; proteiny Drosophily; Energy Metabolism; energetický metabolismus; Metabolism; Lymphoid Tissue; Leptopilina boulardii; Nuclear Proteins; Cell Differentiation; Drosophila; Larva; Animals; Mutation